Comparison of factor of safety using different method of analysis for slope stability / Norfarah Nadia Ismail, Ahmad Bukhari Ramli and Siti Noorliyana Mohd Pami - Ismail, Norfarah Nadia; Ramli, Ahmad Bukhari; Mohd Pami, Siti Noorliyana (Smart Manufacturing Research Institute (SMRI), 2021)
Currently, the construction of slope is increasing, thus, the risk of slope to fail also increase. The series of landslide happen to the man-made slope has been recorded since in the early of 1993 until now. Many efforts such as treating the critical slope, redesigned the failed slope, and analyze the stability of the slope have been done. However, the landslide is still happening in Malaysia. The factor of safety (FOS) from the stability analysis that has been used might not be adequate to determine the safety of the slope in Malaysia. Therefore, in this study, the optimum factor of safety is obtained by using three methods of slice, Bishop’s Simplified method, Spencer method, and Morgenstern-Price method which have been used in many projects. A study place is selected in Ladang Balau, Semenyih, in Selangor and from the CIU test, the important soil parameter for slope is extracted for analysis of slope stability using SLOPE/W and manual calculation. The lambda for Spencer method and Morgenstern-Price method was generated for further discussion on the relationship between lambda and factor of safety. The data generated from both calculation method, from manual and software, were discussed and next the ideal method to achieve the optimum factor of safety determined. The factor of safety for every method basically are influenced by the interslice shear force presence but not Bishop’s Simplified method as moment equilibrium is insensitive towards interslice force function.